Interpersonal Justice and Deviance: The Moderating Effects of Interpersonal Justice Values and Justice Orientation. (February 2013) - Holtz, Brian C.; Harold, Crystal M.
Research suggests that employees who perceive interpersonal injustice in their workplace are more likely to engage in workplace deviance. However, researchers have seldom considered the role of personal values in shaping behavioral reactions to perceived injustice. This article investigates the moderating influence of justice-related values on reactions to perceived injustice. Results suggest that employees with strong interpersonal justice values, or justice orientations, are unlikely to engage in workplace deviance, regardless of their interpersonal justice perceptions. Results were consistent across two operationalizations of justice values and consistent across self-reported and coworker-reported workplace deviance.